Risk factors and treatment of refractory anaphylaxis - a review of case reports. (3rd April 2018) - Francuzik, Wojciech; Dölle, Sabine; Worm, Margitta
ABSTRACT: Introduction : Patients experiencing anaphylaxis who do not recover after treatment with intramuscular adrenaline are regarded as suffering from refractory anaphylaxis. The incidence of refractory anaphylaxis is estimated to range between 3–5% of anaphylaxis cases. The risk factors for refractory anaphylaxis are unknown. Areas covered : In the present analysis, we aimed to evaluate the management and risk factors of refractory anaphylaxis to highlight possible clinical implications for updating current management algorithms. Expert commentary : According to international guidelines, adrenaline given through the intramuscular (i.m.) route is a rapid and safe treatment but may be insufficient. Therefore, defined standardized treatment protocols for such cases of refractory anaphylaxis are needed to optimize the treatment. Point-of-care diagnostics may enable doctors to identify patients experiencing severe, refractory anaphylaxis early in order to initiate intensified critical care treatment.